Au / SiO2 Hybrid Bonding with 6-μm-Pitch Au Electrodes for 3D Structured Image Sensors. (24th August 2016) - Honda, Yuki; Hagiwara, Kei; Goto, Masahide; Watabe, Toshihisa; Nanba, Masakazu; Iguchi, Yoshinori; Saraya, Takuya; Kobayashi, Masaharu; Toshiyoshi, Hiroshi; Higurashi, Eiji; Hiramoto, Toshiro
Abstract : A 3D structured CMOS image sensor that can process signals pixel-wise in parallel is investigated as a means to simultaneously increase the pixel count and the frame rate. To make the pixel pitch finer, the Au electrode dimension is reduced to a 6-μm pitch that is electrically interconnected using a direct-bonding technique. We also develop a daisy-chain test device to examine the numerous interconnections. The experimental results show that the series of electrical interconnections exceeds 230, 000 contacts, with the Au contact resistance for a single connection being 23.6 mΩ.